Estudio del fenómeno de subsidencia en Bogotá, Colombia (2022)
The city of Bogotá is the largest and most populated urban center in Colombia, it is located in a zone of moderate seismicity and due to its complex topography there is a risk of flooding and landslides, and it is also exposed to migratory processes that have been become massive in recent years. The subsidence phenomenon refers to deformation of large areas of the land, this process has affected many cities in the world, bringing serious consequences for their infrastructure and economy. In Bogotá, this problem began to be investigated for about 25 years, the information that has been gradually acquired allows to verify that subsidence is occurring at relatively high rates in the city. In this project, SAR image processing was carried out through the use of SNAP software, obtaining InSAR maps that allowed measuring subsidence rates in Bogotá through the 2016-2019 period, the results were reported and discussed. On the other hand, a review of the state of the art was carried out, in order to compile and summarize the results of previous investigations and existing studies in the literature, on the phenomenon of subsidence in other parts of the world and in particular studies carried out in Bogotá, studies carried out with InSAR interferograms are highlighted to illustrate the potential of the technique and its advantages. The document also exposes geological and geotechnical information on the city of Bogotá and details the steps to follow in the SNAP software for processing SAR images for the generation of InSAR maps.